A Study On Performance Measurement Practices In The Malaysia Manufacturing Sector - Supramaniam, Segar (2009)
This research paper will assess the method, tools and techniques, and the effectiveness of measuring performance in Malaysian manufacturing with wide coverage and across industries from electrical & consumer goods, food and beverages, steel and metal manufacturers, transportation & logistics, construction industries, consumer goods, car manufacturing, wood industries, pharmaceutical and others.